Optimal design of water networks involving multiple contaminants for global water operations - Zainatul Bahiyah, Handani; Sharifah Rafidah, Wan Alwi; Haslenda, Hashim; Zainuddin, Abdul Manan; Sharifah Hanis Yasmin, Sayid Abdullah (John Wiley & Sons, 2011)
This work presents the development of a systematic technique to target the minimum fresh water consumption and wastewater generation to achieve maximum water recovery (MWR) for systems involving multiple contaminants. A generic linear programing (LP) model has been developed based on water network superstructure to simultaneously set the targets and design the MWR network, for both mass transfer‐based (MTB) and non‐mass transfer‐based (NMTB) problems (i.e. global water‐using operations). This work also includes cases where fresh water concentrations for all contaminants are assumed to be either zero or non‐zero. The proposed method is superior since it can guarantee a global optimal solution. Application of the methodology on three case studies shows significant water savings, illustrating the effectiveness of the proposed approach.